Investigation on the steel preheating effects on the aluminium-steel welding - Muhammad Nabil, Abdul Razak (2013)
Dissimilar welding or Tailor Welded Blanks (TWBs) joint is defined as two or more sheets with equal or different materials, thickness, strength, or surface coatings are welded together. The objective of this project is to investigate the effect of heat treatment on the weld joints quality and determine the mechanical properties of the steel-aluminium weld joint. Aluminium alloy AA 6061 was welded with stainless steel SUS 304 in the thickness range of 2mm in lap joint configuration. Among the process parameters varied were filler metal and preheating temperature. By metallurgy cross sections, hardness test and tensile test, the effect of those process parameters on joint properties such as welding joint hardness, macrostructure defect and tensile strength could be elucidated. Based on the results, the penetration of stainless steel with aluminium alloy occurs when the preheating process is applied. Sample C yield the best result in hardness with value at 830HV and 19.91 Mpa in tensile test. The optimum temperature for preheating is 85ºC and by using ER 4043 filler metal.